Adaptasi Beberapa Varietas Unggul Kedelai yang Berdaya Hasil Tinggi dengan Pemberian Dolomit dan Urea di Lahan Pasang Surut - Susilawati Susilawati; Kurniawan Subatra; Rujito Agus Suwigno; Renih Hayati (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Efforts to improve soybean productivity in tidal land, including through land improvement (amelioration) as of lime, use of improved varieties and the fulfillment of plant nutrients. This study aims to determine the adaptation of some soybean varieties for high yield in the tidal land. Research activities conducted in tidal land Banyu Urip Village Subdistrict Tanjung Lago Banyuasin District from July to September 2013 design used is Split Split Plot Design consisting of 3 factors with 3 replications. Main plots were dose Dolomite (D0= 0 ton/ha dolomite, D1= 2 ton/ha dolomite), subplots were dose of urea (P1= 25 kg/ha urea, P2= 50 kg/ha urea, P2= 75 kg/ha urea) and the plot is children soybean varieties (V1= Argomulyo, V2= Anjasmoro, V3= Tanggamus). Variables measured were plant height 17 DAT, plant height 7 MST, leaf chlorophyll and number of branches. The results showed that the varieties that produce Argomulyo plant height, leaf chlorophyll content, and the number of branches is better than the soybean crop varieties Tanggamus and Anjosmoro. Thus soybean varieties are more adaptive Argomulyo planted in tidal land.